Uso de Propofol intracelomatico em tigres do mississipi (Trachemys scripta elegans) - Mouriño, J. M. P.; Vasconcelos, A. S. (Brazilian Journal of Veterinary Research and Animal Science, 2003)
O artigo não apresenta resumo.